Story behind meldonium-from pharmacology to performance enhancement: a narrative review - Schobersberger, W; Dünnwald, T.; Gmeiner, G. (British Journal of Sports Medicine, 2017)
Recent reports from the World Anti-Doping Agency (WADA) indicate an alarming prevalence in the use of meldonium among elite athletes. Therefore, in January 2016, meldonium was added to WADA's prohibited list after being monitored since 2015. Meldonium has been shown to have beneficial effects in cardiovascular, neurological and metabolic diseases due to its anti-ischaemic and cardioprotective properties, which are ascribed mainly to its inhibition of ß-oxidation and its activation of glycolysis. Despite its widespread use, there are only a few clinical studies or clinical trials available. Meldonium is registered in most Baltic countries and is easily accessible through the internet with no serious adverse effects reported by the manufacturer so far. Among athletes, meldonium is used with the purpose of increasing recovery rate or exercise performance. The benefit of taking meldonium in view of performance enhancement in athletes is quite speculative and is discussed without sound scientific evidence. This narrative review provides a detailed overview of the drug meldonium, focusing on the main topics pharmacology and biochemical actions, clinical applications, pharmacokinetics, methods of detection and potential for performance enhancement in athletes.